Ways and distances: a dialogue between childhood psychos and education - Carlos Alberto Garcia Jr; Maria Inês Naujorks (Universidade Federal de Santa Maria (UFSM), 2011)
The theoretical discussion about the links between childhood psychosis and Special Education is recent. Educators, parents and health professionals still face significant difficulties related to the educational processes inclusive of these children. The aim of this study was to make some considerations about the contribution of psychoanalysis to disentangle some these nodes, from the understanding of the subjectivity of children with psychosis. The goal was to go through the various threads of psychoanalytic thinking, ways that allow for dialogue between the approaches and the distancing of production of knowledge about the subject of education/student with childhood psychosis. For this, they plotted a few relationships between these theoretical fields, from a corpus of literature whose analysis included four journals between 1996 and 2008 linked to the education, which are: Revista Brasileira de Educação, Revista Brasileira de Educação Especial, Revista Educação Especial e Revista Estilos da Clínica. We identified 1147 articles, of which only 57 related to the topic, which were directly or indirectly used in this study. It is used as loom freudian-lacanian theory to tie and hold a discussion built upon the selection of state of the art. It was observed that the work explained, in general, speak of a subject in structuring, overwhelmed by a subjectivity. The production on the subject is still incipient, hence the need for more studies and publications. It was noticed, finally, that the contribution of psychoanalysis to education would be the prospect of working with what is not closed, in a time of formation, as look at these children is to see them under construction.